2006
DOI: 10.1002/cmdc.200600201
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of RGD–Albumin Conjugates for Targeted Delivery of the VEGF‐R Kinase Inhibitor PTK787 to Angiogenic Endothelium

Abstract: Linking the unlinkable: Many new chemical entities lack reactive groups for use in the formation of reversible bonds, for example, to conjugate them for targeted drug delivery purposes. We succeeded with the noncovalent coupling of a potent signal transduction inhibitor to a protein backbone by applying the platinum‐based universal linkage system. The resulting drug‐targeting conjugates offer new potential for cancer treatment with minimal side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…The successful formation of a coordinative bond between the platinum (II) linker and the aromatic nitrogen of the pyridine ring in 17864 was proven by mass spectrometry and 195 Pt-NMR analysis. 195 Pt-NMR analysis showed a peak at −2493 ppm which, as has been demonstrated for different drug-ULS-carrier conjugates, 38,39 is characteristic for a Pt-N 3 coordination. The fact that the sunitinib analog SU6668 (ie, the product also contained 14% of the dimeric adduct, ie, (17864) 2 -ULS.…”
Section: Immunostaining Of Fibrotic Markers In Kidney Sectionssupporting
confidence: 68%
“…The successful formation of a coordinative bond between the platinum (II) linker and the aromatic nitrogen of the pyridine ring in 17864 was proven by mass spectrometry and 195 Pt-NMR analysis. 195 Pt-NMR analysis showed a peak at −2493 ppm which, as has been demonstrated for different drug-ULS-carrier conjugates, 38,39 is characteristic for a Pt-N 3 coordination. The fact that the sunitinib analog SU6668 (ie, the product also contained 14% of the dimeric adduct, ie, (17864) 2 -ULS.…”
Section: Immunostaining Of Fibrotic Markers In Kidney Sectionssupporting
confidence: 68%
“…We recently developed a versatile linking technology, the so-called Universal Linkage System (ULS), for the coupling of drugs to carrier systems, 20,21,23,24 which we now have applied for the conjugation of the Rho kinase inhibitor Y27632 to LZM. We investigated the potential activity of Y27632-LZM in the ischemia-reperfusion (I/R) injury model and demonstrated both enhanced activity and increased selectivity of the tubular-targeted Rho kinase inhibitor.…”
mentioning
confidence: 99%
“…195 Pt-NMR analysis of 17864-ULS showed a peak at d ¼ -2493, characteristic for Pt-N 3 coordination, [35] confirming the coupling of the ULS linker to one of the nitrogen atoms present in 17864. The observation that (Z)-3-{2,4-dimethyl-5-[(2-oxoindolin-3-ylidene)methyl]-1H-pyrrol-3-yl}propanoic acid (i.e., the sunitinib analogue SU6668) cannot be coordinated to the ULS linker (data not shown), indicates that a coordinative bond is formed between the platinum atom of the linker and the pyridine nitrogen in 17864.…”
Section: Synthesis and Characterization Of 17864-uls-nh 2 -Pamam-g3mentioning
confidence: 90%
“…In vivo biodistribution studies have shown that kinase inhibitor-ULS-carrier conjugates reside in the designated cells for several days and that the majority of the accumulated kinase inhibitor is present in the ULS-bound form. [33][34][35][36] Because sunitinib cannot be coordinated to the ULS linker, we synthesized a sunitinib analogue, that is, 17864, that has an extended pyridyl side chain. When the ATP-competitive kinase inhibitor sunitinib binds to its target kinases the oxindole moiety of sunitinib is localized deep in the ATP-binding pockets of the target kinases, while the N-2-(diethylamino)ethylene moiety is protruding outwards.…”
mentioning
confidence: 99%